HERMENEUTIKA DAN ETIKA NARATIF MENURUT PAUL RICOEUR - M. Sastrapratedja (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
After his retirement, Paul Ricoeur published his three-volume works, Time and Narrative (Chicago: Chicago University Press, 1984 1985). For Ricoeur, time becomes human's time when it is organized in a narrative. Narrative becomes meaningful when it portrays the feature of temporal experience. The present article tries to show that a narrative requires an interpretation. Paul Ricoeur's hermeneutics consists of two stages, distanciation and appropriation. Distanciation enables the reader to study the text critically and then it must be followed by a post-critical reading where the reader appropriates the world opened to him. In the words of Gadamer, in the process of interpretation, the horizon of the text fuses with the horizon of the reader. In reading narrative, the identity as ipse and as idem interacts each other. The narrative ethics does not contradict with the normative ethics, later gives validation to the former one. In the case of a conflict, then responsibility shoud be the priority